Analisis Kemampuan Pemecahan Masalah Pada Materi Fungsi Melalui Penerapan Model Pendidikan Matematika Realistik - Lubur, Dorothea Novia Ludo (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to determine the problem solving skills of IX grade students of SMPK St. Paulus on the material functions with the Realistic Mathematics Education approach. The method used in this research is descriptive qualitative. The subjects in this study consisted of 10 students of class IX. Students' answers are analyzed and classified according to the type of answer. The following student answers consist of 5 different types of answers. Seven students with the first, second and fourth types of answers fulfill four indicators. One student with the third type of answer only reaches two indicators namely the first and second indicators, and one student with the fifth answer type fulfills three indicators namely the first, third and fourth indicators. Based on the results of the analysis it can be concluded that there are 80% of students fulfilling the four indicators of NCTM, 10% of students do not meet the third and fourth indicators and 10% of students do not meet the second indicator